Financial Mismanagement of Small Businesses: A Study Based on The Hotel Industry in Nuwara Eliya District - Kariyakarawana, K.I.P.; Panditharathna, K.M.; Ranwala, R.S.; Nimeshi, G.K.S. (University of Jaffna, 2023)
The purpose of the study was to identify the financial mismanagement of small businesses and their effect on the business’s success. This research used the qualitative approach and continued the study through the general qualitative method. Sample were selected based on the purposive sampling method. Accordingly, data collection was done through in-depth interviews with owners of six small businesses in the Talawakele - Lidula Municipal Council area in the Nuwara Eliya District. The data were analysed, and themes were derived using thematic analysis. The main mismanagement identified from the study was mismanaging start-up capital, cash flows, budgetary system, personal spending, retained earnings, and working capital. Due to these mismanagements, businesses cannot run with a proper plan. The findings of this study will enable small businesses to identify their financial mismanagement. These findings will also help policymakers to identify the areas that are required to improve the financial management literacy of small business owners.
Keywords: Financial Mismanagement; Qualitative; Small Businesses; Hotel Industry